Marriages & families : intimacy, diversity, and strengths - DeFrain, John; Olson, David H. (Boston : McGraw Hill, 2006)
Contenido: The social context of intimate relationships. Perspectives on intimate relationships. Cultural diversity: family strengths and challenges. Understanding marriage and family dynamics. Dynamics of intimate relationships. Communication and intimacy. Conflict and conflict resolution. Sexual intimacy. Gender roles and power in the family. Managing economic resources. Stages of intimate relationships. Friendship, intimacy, and singlehood. Dating, mate selection and living together. . Marriage: building a strong foundation. Parenthood: choices and challenges. Midlife and older couples. Challenges and opportunities. Stress, abuse and family problems. Divorce, single parent families and stepfamilies. Strengthening marriages and families.